Factors associated with relapse and recurrence of major depressive disorder in patients starting mindfulness‐based cognitive therapy. Issue 2 (9th November 2021) - de Klerk‐Sluis, Jessica M.; Huijbers, Marloes J.; Löcke, Stephan; Spijker, Jan; Spinhoven, Philip; Speckens, Anne E. M.; Ruhe, Henricus G.
Abstract: Background: Mindfulness‐based cognitive therapy (MBCT) is effective for relapse prevention in major depressive disorder (MDD). It reduces cognitive reactivity (CR) and rumination, and enhances self‐compassion and mindfulness. Although rumination and mindfulness after MBCT are associated with relapse, the association of CR, rumination, self‐compassion, and mindfulness with relapse before initiation of MBCT has never been investigated. Methods: Data were drawn from two randomized controlled trials, including a total of 282 remitted MDD participants (≥3 depressive episodes) who had been using maintenance antidepressant medication (mADM) for at least 6 months before baseline. All participants were offered MBCT while either their mADM was maintained or discontinued after MBCT. CR, rumination, self‐compassion, and mindfulness were assessed at baseline by self‐rated questionnaires and were used in Cox proportional hazards regression models to investigate their association with relapse. Results: CR and mindfulness were associated with relapse, independent of residual symptoms, previous depressive episodes, and mADM‐use. Higher CR and lower mindfulness increased the risk of relapse. Self‐compassion was not associated with relapse. For rumination, a significant interaction with mADM‐use was found. Rumination was associated with relapse in patients who discontinued their mADM, while this effect was absent if patients continued mADM. Conclusions: These results show that CR, rumination, and mindfulness are associated with relapse in remitted MDD‐patients before initiation of MBCT, independent of residual symptoms and previous depressive episodes. This information could improve decisions in treatment planning in remitted individuals with a history of depression.